The woman who named God: encountering Hagar in a mental health facility - Beresford, Anna (2024)
Set within the biblical narrative of Sarah and Abraham is the figure of Hagar – Sarah’s slave. The significance of Hagar is often overlooked. This article re-examines her story and identifies her own matriarchal status as an intelligent and resourceful woman of faith. Noting that God and Hagar knew each other by name, the author (an experienced hospital chaplain) demonstrates how Hagar’s experience can help both clinicians and patients in a mental health environment. Hagar is a model of transcendence – living above the circumstances that hinder our abilities to flourish.
Keywords: Story; Name; Mental Health; Healing; Hagar